YURIDIS ANALISA QUICK RESPONSE CODE SEBAGAI SISTEM PEMBAYARAN DITINJAU DARI PERATURAN BANK INDONESIA NOMOR 18/40/PBI/2016 TENTANG PENYELENGGARAAN PEMROSESAN TRANSAKSI PEMBAYARAN - Meiliana Paramitha Utami; Bernadetta Tjandra Wulandari (Program Magister Ilmu Hukum Universitas Pancasila, 2021)
Countries in the world including Indonesia are increasingly developing from various aspects ofculture, health, economy, and continue to improve increasingly sophisticated technology. Banksin the aspect of the nation's economy have an important role as financial institutions that caninfluence the economic activities of a nation and play an active role in the progress anddeterioration of a nation's economy. The Quick Response Code is the latest innovation in theIndonesian banking industry to facilitate customers in conducting transactions, namely byconducting transactions using QR Code (barcode). This feature makes it easy for customers tosimply scan (barcode) the sticker / receipt from the merchant. The author's method that I use isnormative juridical. The author discusses how the application of risk management and legalprotection for QR Code users. Although the service and Implementation Regulations for the QRCode have been used by customers, these regulations must be discussed again and reformulatedwith regard to the protection and accountability of users of the QR Code and clear sanctions inthe event of losses caused by fraudsters. Complaint efforts in the event of a loss to the QR Codeuser, can submit complaints to Bank Indonesia as long as they meet these requirements